2015
DOI: 10.1097/igc.0000000000000306
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular Space Invasion and the Treatment of Stage I Endometrioid Endometrial Cancer

Abstract: In stage I LVSI-positive EEC with 0 to 1 risk factors, observation might not be adequate. Moreover, despite adjuvant radiotherapy, a high overall and distant recurrence rate was observed in patients with 2 to 3 risk factors. The use of systemic treatment in these patients, with the exception of patients with grade 1 disease, should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…However, it should be emphasized that the prognostic significance of lymphovascular space invasion detected by hematoxylin and eosin, and diagnosed by the primary pathologist, has already been demonstrated in a multicenter study including lymphovascular space invasion-positive patients with stage I endometrioid endometrial cancer 24. By contrast, the absence of quantification of lymphovascular space invasion such as ‘absent’, ‘focal’, and ‘substantial’25 seems to be another important limitation of our study, since substantial lymphovascular space invasion has been reported as a significant factor for recurrence in endometrial cancer 25…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be emphasized that the prognostic significance of lymphovascular space invasion detected by hematoxylin and eosin, and diagnosed by the primary pathologist, has already been demonstrated in a multicenter study including lymphovascular space invasion-positive patients with stage I endometrioid endometrial cancer 24. By contrast, the absence of quantification of lymphovascular space invasion such as ‘absent’, ‘focal’, and ‘substantial’25 seems to be another important limitation of our study, since substantial lymphovascular space invasion has been reported as a significant factor for recurrence in endometrial cancer 25…”
Section: Discussionmentioning
confidence: 99%
“…18 As the probability of lymph-node involvement is low, avoidance of unnecessary lymphadenectomy is mandatory bearing in mind the invasive nature. 18 Considering the current and previous studies, 14,15 it may be that adjuvant RT does not improve recurrence rates in patients with LVSI. This is most likely due to distant recurrences.…”
Section: Discussionmentioning
confidence: 90%
“…20,23,26,27 It has been validated as the (78) strongest independent prognostic factor, 21,28 associated with poor oncological outcomes and reduced survival time. 20,25,29,30 So it should be observed when possible to identify a risk group in which lymphadenectomy and/or adjuvant therapy are beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…29 In 1 study in the Netherlands, in stage I EC with positive LVSI with no lymphadenectomy, radiotherapy (RT) was not enough to prevent distant recurrences. 27 Despite adjuvant therapy with pelvic RT, a significant number of patients still have distant metastases 27,29 ; therefore, adding CT to RT may provide added therapeutic benefit. 34,38 However, its benefit in terms of survival remains controversial in early-stage diseases, and there are no data of its advantage in positive LVSI.…”
Section: Discussionmentioning
confidence: 99%